Marketing Strategy Development for Belvoir Castle Corporate and Private Events - Limb, Andrew T (2009)
Belvoir Castle in North Leicester has in recent times begun to offer corporate hospitality products. The Corporate Hospitality Team pride themselves on offering high-end corporate products in a prestigious location, with a wide range of configuration options.